PENGEMBANGAN INSTRUMEN PENGUKUR KECERDASAN EMOSIONAL SISWA BERBAKAT INTELEKTUAL - MISYKAT MALIK IBRAHIM (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2012)
This research study aims for finding of: (1) the construct underlying the instrument to measure the emotional intelligence of the intellectually gifted students, (2) the measurement instrument satisfying the construct validity requirement, (3) the factors being constructed from the measurement instrument, and (4) the measurement instrument satisfying the reliability requirement. Conseptually, the construct of the emotional intelligence of the gifted students consists of two domains, namely: (1) the emotional intelligence qualified as being intrapersonal along with self-awareness, self-regulation, self motivation dimensions, and (2) the emotional intelligence qualified as being interpersonal along with emphaty dimensions and working together. Of the items being validated by using expert judgement with the coefficient reliability of 0,89 and the other eighty six items are selected for the instrument to measure the emotional intelligence of the intellectually gifted students. Empirically, the factor analysis using the method of Maximum Likelihood successfully has extracted sixty nine factors in the first try out and sixty five factors in the second try out. The reliability test suggests that bacause the alpha stratified coefficient for multidimensions is 0,815 of the measurement instrument is strongly reliable. The most significant finding of this research is the instrument to measure the emotional intelligence of the intellectually gifted students has an appropriate construct validity and internal consistency.